Hubungan Kecemasan Dengan Gangguan Siklus Menstruasi Pada Siswi Kelas XII Sma Negeri 1 Surakarta - Anisa Febrina Damastuti; Rosalia Sri Hidayati; Arif Suryawan (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background : The number of people who suffer anxiety was estimated to be 5% of population, with the ratio off women and men is 2:1. Emotional breakdown, tension, presure, and agitation could lead to disruption of menstrual cycle. The purpose of this study was to determine the correlation of anxiety and mestrual cycle disorder on grade XII female student of SMA Negeri 1 Surakarta. Methods : This study was an observational analytic with cross sectional study approach. The sampling technique used was purposive sampling. Sample was as many as 82 subjects, taken from the grade XII female students of SMA Negeri 1 Surakarta, and was hold on August 2012. Data were obtained by TMAS and menstrual cycle questionnaires. The statistical analysis used was chi-square. Results : Chi square calculation obtained X2 > X2 table = 7,142 > 3,841. The number showed a significant association. Conclusion : Based on this study it could be concluded that there was a positive relationship between anxiety and mestrual cycle disorder on grade XII female student of SMA Negeri 1 Surakarta. Keywords : anxiety, menstrual cycle, menstrual cycle disorder